Life in groups: the roles of oxytocin in mammalian sociality - Anacker, Allison; Beery, Annaliese (Frontiers in Behavioral Neuroscience, 2013)
In recent decades, scientific understanding of the many roles of oxytocin in social behavior has advanced tremendously. The focus of this research has been on maternal attachments and reproductive pair-bonds, and much less is known about the substrates of sociality outside of reproductive contexts. It is now apparent that oxytocin influences many aspects of social behavior including recognition, trust, empathy, and other components of the behavioral repertoire of social species. This review provides a comparative perspective on the contributions of oxytocin to life in mammalian social groups. We provide background on the functions of oxytocin in maternal attachments and the early social environment, and give an overview of the role of oxytocin circuitry in support of different mating systems. We then introduce peer relationships in group-living rodents as a means for studying the importance of oxytocin in non-reproductive affiliative behaviors. We review species differences in oxytocin receptor distributions in solitary and group-living species of South American tuco-tucos and in African mole-rats, as well as singing mice. We discuss variation in oxytocin receptor levels with seasonal changes in social behavior in female meadow voles, and the effects of oxytocin manipulations on peer huddling behavior. Finally, we discuss avenues of promise for future investigation, and relate current findings to research in humans and non-human primates. There is growing evidence that oxytocin is involved in social selectivity, including increases in aggression toward social outgroups and decreased huddling with unfamiliar individuals, which may support existing social structures or relationships at the expense of others. Oxytocin’s effects reach beyond maternal attachment and pair bonds to play a role in affiliative behavior underlying “friendships,” organization of broad social structures, and maintenance of established social relationships with individuals or groups.